Techno-functional, nutritional, and health-promoting properties enhancement of mopane worm and orange-fleshed sweet potato flour blends via ultrasonication and controlled fermentation - Molimi, Mpho Brian; Adebo, Oluwafemi Ayodeji (Frontiers in Microbiology, 2025)
This study investigated the impact of fermentation and ultrasonication on biochemical, nutritional, and health-promoting properties of mopane worm (MP) and orange-fleshed sweet potato (OFSP) flours, followed by nutritional, health-promoting, pasting, and thermal properties of their subsequent blends, derived from three MP: OFSP blending ratios (60:40, 55:45, and 45:55) for each processing technique. Respective flour was fermented using starter culture (mesophilic lactic acid bacteria) for 48 h at 35 °C and ultrasonicated at 500 W, 20 kHz for 5 min. Both processes significantly reduced pH and increased the total titratable acids (TTA) of all flours. Increments in protein, ash, and total flavonoid content (TFC) were observed in all fermented flours, while ultrasonicated flours exhibited elevated fiber and total phenolic content (TPC). Unlike ultrasonication, fermentation reduced the 2,2-Azinobis (3-ethyl-Benzothiazoline-6-sulfonic acid) (ABTS) of all flours. After blending processed MP and OFSP flours, there were beneficial modifications in the in vitro starch digestibility of their resultant blends. For instance, the addition of 60% MP significantly reduced (p < 0.05) rapidly digestible starch (RDS) in fermented blends, while ultrasonicated blends had lower total digestible starch (TDS). The TFC, TPC, and ABTS of all the blends varied from 3.83 to 5.06 mgQE/g, 1.90–2.76 mgGAE/g, and 52.93–61.03%, respectively. Higher peak viscosity in fermented blends reflects good water-binding capacity and the ability to produce a highly viscous gel. Intrinsic alterations in thermal properties were observed in fermented blends, involving the reduction of onset and peak temperatures. The present study revealed that both fermented and ultrasonicated blends containing 60% MP and 40% OFSP flour had beneficial complementary properties, which may be excellent for the development of novel food products with improved health and nutritional advantages.